2019
DOI: 10.1029/2018jb017128
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Magnetic Fabrics at Low Shock Pressure Due to Experimental Impact Cratering

Abstract: Magnetic fabrics provide important clues for understanding impact cratering processes. However, only a few magnetic fabric studies for experimentally shocked material have been reported so far. In the framework of MEMIN (Multidisciplinary Experimental and Modeling Impact Research Network), we conducted two impact experiments on blocks of Maggia gneiss with the foliation oriented perpendicular (A38) and parallel (A37) to the target surface. Maggia gneiss has plenty of biotite bands forming a strong rock foliati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…On the other hand, present observations agree with the trends in cratering experiments. Here experimental shock pressure (< 3 GPa) increases the bulk magnetic susceptibility of rocks with small magnetite grains, < 10 µm (Agarwal et al 2019). Although the mechanism behind this increase is not known, their results agree well with the present observations.…”
Section: Variation In Bulk Magnetic Susceptibilitysupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, present observations agree with the trends in cratering experiments. Here experimental shock pressure (< 3 GPa) increases the bulk magnetic susceptibility of rocks with small magnetite grains, < 10 µm (Agarwal et al 2019). Although the mechanism behind this increase is not known, their results agree well with the present observations.…”
Section: Variation In Bulk Magnetic Susceptibilitysupporting
confidence: 90%
“…Until now, the shock demagnetization of magnetic minerals such as magnetite, Ti-magnetite, hematite, Ti-hematite, and pyrrhotite (see Louzada et al 2011 and the references therein) was the only effect of low shock pressures (< 3 GPa), which was considered of importance at a regional scale. However, now, increase in magnetic susceptibility of Ti-magnetite, at low shock pressures, is clear from present investigations Table 1 Table compiles the on naturally shocked target basalts at Lonar impact structure, and from experiments (Agarwal et al 2019).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In agreement to the reorientation of the magnetic fabrics, the Vertical Profile of A38 shows intense straining, which is lower on either side, in the Left and Right Oblique Profiles of A38. Agarwal et al (2019) show that in A37 (horizontal foliation) the reorientation of the magnetic fabrics is less below the crater, but more at the sides. A similar trend is seen in the present study.…”
Section: Control Of the Foliation On The Compressive Strainmentioning
confidence: 88%
“…Hence, based on these experiments it can be concluded that the shock pressure generated due to impact has affected the rock magnetic properties of the target basalts presently exposed around Lonar crater rim and surrounding areas (Arif et al 2012b). Agarwal et al (2019), in their recent experiments on gneissic target, show that the reorientation of magnetic fabrics is possible at shock pressure as low as 0.1 GPa. This experiment is perhaps not analogous to Lonar impact because like the gneissic target, Lonar target basalt does not have a strong preimpact magnetic fabric that could influence the orientation of AMS axes due to impact.…”
Section: Shock Pressure and Rock Magnetic Properties Of Lonar Crater Rim Basaltsmentioning
confidence: 98%